Using a single product (calcipotriene/betamethasone topical suspension) vs multiple products to manage body and scalp psoriasis: comparisons in resource utilization and costs. (December 2013) - Feldman, Steven R.; Levi, Eugenia; Pathak, Prathamesh; Kakatkar, Sonali; Balkrishnan, Rajesh
Abstract Objectives: To compare resource utilization and costs among patients who used calcipotriene/betamethasone dipropionate topical suspension (Taclonex Scalp Topical Suspension, Leo Pharma A/S) vs those who used multiple body and scalp formulations for psoriasis. Research design and methods: A retrospective study using Truven Health MarketScan Commercial Database from 2006–2011 was performed to identify patients with psoriasis (ICD code 696.1x). Two study cohorts analyzed were cohort A (used body-only formulations for psoriasis and switched on the index date to using calcipotriene/betamethasone dipropionate topical suspension alone) and cohort B (used multiple body and scalp formulations for psoriasis). Patients were required to be continuously enrolled during 180-days pre- and post-index periods. Multiple regression analyses adjusting for baseline demographic and clinical covariates were performed. Main outcomes measures: Number of psoriasis-related outpatient visits, total healthcare costs, psoriasis-related costs, and use of systemic agents during post-index period. Results: A total of 1923 patients were identified with at least one prescription for calcipotriene/betamethasone dipropionate scalp topical suspension (cohort A = 367, cohort B = 1556). Patients using multiple medications (cohort B) were associated with 48% higher number of outpatient visits as compared with those who used a single formulation (cohort A) after controlling for baseline covariates (p < 0.001). A generalized linear model adjusting for baseline covariates showed significantly higher post-index total and psoriasis-related healthcare costs for cohort B as compared with cohort A (both p < 0.001). Patients in Cohort B also had twice the odds of using systemic agents as compared to patients in Cohort A (p < 0.001). Conclusions: Patients with body and scalp psoriasis using a single product had significantly lower overall and psoriasis-related healthcare costs, needed fewer psoriasis-related outpatient visits, and used less systemic agents during the post-index period. A lack of robust clinical measures to define the disease severity may have limited the interpretations from this study.